Single-cell transcriptomics reveals predominantly inflammatory endothelial cell responses and suppressed vascular repair in silicosis - Cao, Dongli; Cui, Huashun; Chen, Zequan; Li, Heyang; Li, Bing; Wang, Jianhua (Frontiers in Immunology, 2025)
IntroductionSilicosis is a progressive fibrotic lung disease without effective treatment options, and its pathogenesis remains incompletely understood, particularly the role of endothelial cells (ECs).MethodsHere, we utilized single-cell RNA sequencing to characterize endothelial responses in lungs from silica-exposed mice.ResultsWe identified two functionally distinct endothelial subpopulations: 1. An inflammatory EC subtype, exhibiting significantly increased abundance and characterized by high expression of neutrophil-recruiting factors such as Spp1 (osteopontin), CCL (C-C motif chemokine ligand), and ESAM (endothelial cell–selective adhesion molecule), suggesting active involvement in neutrophil influx and persistent inflammation. 2. A reparative EC subtype, marked by upregulation of angiogenesis and vascular repair pathways, which exhibited decreased abundance and functional suppression within the silicotic lung microenvironment.DiscussionThese results indicate a pathological shift toward inflammation-amplifying endothelial cells and impaired reparative capacity during silicosis progression. Our findings provide new mechanistic insights into endothelial cell dysfunction in silicosis and highlight potential targets for therapeutic intervention.